Investigation of kerf in micro wire electro discharge machining - Ali, Mohammad Yeakub; Khamarruzaman, Siti Nur Zalikha; Banu, Asfana (IOP Publishing, 2017)
Precision and accuracy are among those of the most important factors in the field of machining processes. Micro wire electro discharge machining (micro-WEDM) is used widely in the machining process to fabricate micro parts with high precision and accuracy. However, in micro-WEDM, minimal kerf remains as a critical issue. This paper investigates the kerf in micro-WEDM of stainless steel (S304). Experimental investigation is carried out with 70 μm diameter tungsten electrode wire with two varying parameters voltage and capacitance. The kerf data are analyzed and an empirical model is developed using Design Expert software. The optimum parameters for minimum kerf are found to be 10nF capacitance and 90V voltage.